Container loading problem model development considering weight distribution - Amelia, Anisa; Ma'aruf, Anas; Saputra, Tezar Yuliansyah (2010)
One of the biggest problems in logistic operation is material handling. By having good material handling, product demanded by costumer can reach the costumer’s hand without any or with less damage. Container is one of material handling tools designed to move materials in one big unit load, but the container stability in weight is a problem that has to be considered for the safeties and easiness when the container will be transported to another place or location. This paper proposes an analytical model to optimize the weight distribution in one container. The model has capability in optimizing the cargo position inside the container to get the most stable cargo weight distribution.A case study example is also presented to illustrate the model.